Children’s learning for sustainability in social studies education: a case study from Taiwanese elementary school - Shih, Yi-Huang (Frontiers in Education, 2024)
The primary aim of social studies education is to convey knowledge about cultural and social systems while fostering inquiry, participation, practice, reflection, and innovation. Social studies education plays a pivotal role in raising awareness about various ethnic groups, societies, localities, countries, and the world at large. Furthermore, it instills in students a sense of responsibility, leading them to embrace diversity, value human rights, and promote global sustainability. The current elementary social studies curriculum in Taiwan strongly aligns with these principles and is a vehicle for sustainable development in society. This study reviewed the pedagogical design of the elementary social studies curriculum in Taiwan as a means of sustainability education and enriching children's cultural learning in the context of sustainability. Children's learning related to sustainability in an elementary school was investigated, and a social studies teaching design was developed. Finally, the developed teaching approach was implemented in a classroom setting. The study yielded the following findings: (1)The social studies curriculum development in Taiwan is connected to the pulse of life, a sense of care for local communities, and cultivation of local thinking. (2) This social studies curriculum adopts a child-centered and problem-oriented approach and integrates students' interests and the local environment into the learning process. (3) It effectively enhances students' sustainability-related competencies and skills. These findings offer valuable insights for teachers and can enable them to shape the direction of their social studies courses and cultivate children's concept of sustainable development for their living enviroment.